Analisis Penerapan Sistem Informasi Akuntansi Penjualan Perumahan Dalam Meningkatkan Pengendalian Internal Perusahaan Properti Pada PT. Anugrah Reveno Lestari Abadi (PT. Arla) Kota Medan - Rahmalisa Oktadila; Muhammad Arif; Kusmilawaty Kusmilawaty (Journal of Islamic Economics and Finance, 2023)
This research was conducted at a company operating in the property sector, called PT. Anugrah Reveno Lestari Abadi which is usually abbreviated as PT. ARLA. This research aims to find out how the sales accounting information system is implemented and how the sales accounting information system is implemented in improving internal control at PT. ARLA Medan City. This research method uses a qualitative method with a descriptive approach. The type of data used is primary data obtained from interviews and secondary data obtained from documentation. This research uses data collection techniques by interviewing several employees at PT. ARLA. The results of this research indicate that the implementation of the sales accounting information system at PT. ARLA has been running quite well. However, there are several weaknesses, such as still using an accounting system that is not yet computerized properly and there are also still duties between related information functions that are not in accordance with the elements of internal control so that the company's internal control has not been able to improve.